Noncrystallographic symmetry‐constrained map obtained by direct density optimization. Issue 2 (10th February 2020) - Yoshimura, Masato; Chen, Nai-Chi; Guan, Hong-Hsiang; Chuankhayan, Phimonphan; Lin, Chien-Chih; Nakagawa, Atsushi; Chen, Chun-Jung
Abstract : A noncrystallographic symmetry‐constrained map obtained by direct density optimization is efficient and equivalent to a noncrystallographic symmetry‐averaging map. Using the noncrystallographic symmetry‐constrained map, the structure of a T = 1 Penaeus vannamei nodavirus shell‐domain subviral particle was newly determined by including twinned data. Abstract : Noncrystallographic symmetry (NCS) averaging following molecular‐replacement phasing is generally the major technique used to solve a structure with several molecules in one asymmetric unit, such as a spherical icosahedral viral particle. As an alternative method to NCS averaging, a new approach to optimize or to refine the electron density directly under NCS constraints is proposed. This method has the same effect as the conventional NCS‐averaging method but does not include the process of Fourier synthesis to generate the electron density from amplitudes and the corresponding phases. It has great merit for the solution of structures with limited data that are either twinned or incomplete at low resolution. This method was applied to the case of the T = 1 shell‐domain subviral particle of Penaeus vannamei nodavirus with data affected by twinning using the REFMAC 5 refinement software.